Pelatihan Speaking Dasar Dan Fungsional Untuk Relawan Muda Dan Pemuda Riau - Agung Prasetyo Wibowo; Prih Febtiningsih; Pahmi Pahmi; Ardiya Ardiya; Wandi Syahfutra; Siti Niah (Jurnal Pengabdian UntukMu NegeRI, 2020)
The basic speaking training community service program which is one of the pillars in Higher Education Institution such as Universitas Muhammadiyah Riau is carried out aimed at providing an overview of the importance of knowledge about English and motivation concerning the mastery of English. This was done to make it easier for trainees to understand how certain expressions and vocabulary can be applied in international activities such as the International Youth Exchange Program, International Internships, Scholarship Interviews and so forth. Based on these objectives, the target to be achieved in this program is to provide knowledge of the participants, to develop the ability to speak English so that they can pass international programs, scholarships and continue their postgraduate degree. To achieve the goals and targets of community service activities, the implementers use lecture, discussion, think pair and share, and problem-based learning methods, so that the trainees can easily understand the material provided. The activities carried out and participated by program participants came from various University and Higher Education graduates in Riau. The training participants were very enthusiastic about participating. This was evidenced by the large number of participants who were active in the discussion and enthusiastic in taking the activities.